ANALISIS EFISIENSI RELATIF PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH DI PROVINSI MALUKU UTARA TAHUN 2008-2010 - , Hamdani Pora, Dr. M. Edhie Purnawan, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this study is to analyze relative efficiency in performance on budget allocation of the 2008-2010 Local Budget of ecah Local Government Working Unit (Satuan Kerja Perangkat Daerah-SKPD) of North Moluccas Province. An analysis instrument used was Data Envelopment Analysis (DEA). It was run by identifying all SKPDs whose inputs and outputs will be evaluated. Moreover, productivity value was calculated and all SKPDs were identified to find out SKPDs that did not use inputs efficiently or not produce outputs effectively. The productivity measured was comparative or relative in nature, because it only compared interunit measurements from a set of the sama data. Result of the analysis indicates that based on the Data Envelopment Analysis (DEA) using the assumptions of constant returns to scale (CRS) from twenty nine SKPDs in North Moluccas Province, only one SKPD was relatively efficient for three years of observation, while using the assumptions of variable returns to scale (VRS) nine SKPDs were relatively efficient for three years of observations. It shows that all SKPDs were relatively appropriate in the use of inputs compared to other SKPDs.